The Role of Acupuncture in Relieving Post-Hemorrhoidectomy Pain: A Systematic Review of Randomized Controlled Trials - Chen, Huan; Zhang, Weina; Sun, Yuanjie; Jiao, Ruimin; Liu, Zhishun (Frontiers in Surgery, 2022)
Background Post-hemorrhoidectomy pain (PHP) remains one of the complications of hemorrhoidectomy and can delay patient's recovery. Current clinical guideline on PHP remains skeptical on the effectiveness of acupuncture, which has been applied for PHP in practice with inconsistent evidence. Objectives This systematic review aimed to evaluate the effectiveness of acupuncture on PHP by reviewing existing evidence. Methods Nine databases such as PubMed and Embase were searched for randomized controlled trials (RCTs) from inception to 30th September 2021. The outcome measures on pain level after hemorrhoidectomy, dose of rescue analgesic drug used, quality of life, adverse events, etc., were extracted and analyzed in a narrative approach. Results Four RCTs involving 275 patients were included in the analysis. One study showed that the visual analog scale (VAS) score was significantly lower in the electro-acupuncture (EA) group compared to that in the sham acupuncture (SA) group at 6, 24 h after surgery and during the first defecation (p < 0.05). Similar trends were found in the verbal rating scale (VRS) and Wong-Baker Faces scale (WBS) score but at different time points. Another study also found EA was effective on relieving pain during defecation up to 7 days after surgery when compared with local anesthetics (p < 0.05). However, two studies evaluating manual acupuncture (MA) compared with active medications for PHP showed inconsistent results on effectiveness. Variability was found in the quality of included studies. Conclusions Although benefit of acupuncture on PHP, especially EA on defecation after surgery, was observed at some time points, evidence on effectiveness of acupuncture on PHP was not conclusive. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/, PROSPERO, identifier: CRD42018099961.